Language variables in administrative health data hosted at ICES - Batista, Ricardo; Prud'homme, Denis; Tanuseputro, Peter; Manuel, Doug (L'institut du Savoir Monfort and ICES Ottawa, 2019)
Research on linguistic minorities have revealed important disparities in Canada. Numerous analyses have identified the need for further studies looking at health status, healthcare utilization access barriers and quality of care affecting francophone living in a minority contexts (FLMCs) in Canada.1 The value and need to improve access and use of valid health information to support the planification of health and social services is well documented; however, important gaps and challenges have been recognized, which limit further progress in understanding the disparities in health and health care for some subpopulations. 2

The health impact of living in a nursing home with a predominantly different spoken language - Batista, Ricardo; Prud’homme, Denis; Hsu, Amy T.; Guérin, Eva; Bouchard, Louise; Rhodes, Emily; Talarico, Robert; Desaulniers, Jacinthe; Manuel, Douglas; Tanuseputro, Peter (Journal of the American Medical Directors Association, 2019)
Abundant research shows that linguistic barriers can have a negative impact on access to and quality of health care, as well as a patient's health outcomes.1–3 Establishing a culturally appropriate environment, by providing care to nursing home residents in their preferred language, is key in providing good-quality long-term care (LTC) services.4,5 French is one of Canada's 2 official languages. In Ontario, Canada, studies using population-based data have shown that Francophones have a lower perception of good health, higher prevalence of chronic diseases, and greater dependency on LTC services compared to Anglophones.6,7 However, the impact of language discordance on the outcomes of residents in nursing homes has not been previously explored.